The Use of Promoting Questions in Play Activities with the Playworld Approach in Kindergarten - widya Sari, winda; Yus, Anita; Husna Handayani, Peny; Afria Damayanti, Nina (Exploration in Early Childhood Research, 2024)
The current challenge for teachers is how learning in Kindergarten (TK) through play can help children acquire an understanding of a concept. This study aims to explain the use of promoting questions, identify the types of promoting questions that can help children understand a concept, and explain the process by which promoting questions help children understand the concept of "fermentation" through the play activity "Making Bread" using the Playworld approach. Data was collected through observation of 5 recordings of play-based project learning with the Playworld approach, with an average duration of 75 minutes per recording, observing the behaviour of nine children and one teacher. The data was analysed based on cultural-historical theory, which shows that the teacher used promoting questions during the children's play activities, both individually and in groups. These promote questions aimed at developing children's thinking abilities, such as "What are you doing?" and "Look, what is happening?" Additionally, teacher questions need to encourage and direct children to think to understand the material, such as "What is happening with the dough in that jar? Let's see, what is happening, does it smell?" Then the teacher asks, "What can you do with that dough?" The use of promoting questions helps maximise children's imaginative play into experiences that allow them to learn various subjects and understand the concepts of "fermentation, numbers and quantities, and shapes" in the "Making Bread" play activity with the Playworld approach. Promoting questions are used by the teacher when "playing" as the children's friend. The objectives of promoting questions can be categorised into (1) investigating further (explore), (2) expanding (extend), (3) involving or engaging (engage), and (4) reflecting. The implication of this research is the use of promoting questions as part of play pedagogy.